On-farm bean grain quality testing for smallholders in Honduras - Irias, D.; Salinas, D.; Reyes, B. (CGIAR System Organization, 2024)
A novel service for smallholder farmers consisting of quick, on farm bean grain quality testing with low-cost, mobile test kits operated by local technicians from farmer organizations. Currently, grain testing is done centrally at the association’s warehouse or processing facility, and this process needs to be clarified for the farmers. To make the quality-testing process more transparent and create awareness of bean quality and price determination, we will perform at-farm (on-site, with the farmer) bean grain quality testing focusing on the top three quality parameters typically evaluated later at the processing facility. Local technicians from the associations will be trained and perform the test on-farm. They will register the test results using an electronic form automatically delivered to CIAT and the Associations and leave a printed copy to farmers. Farmers will be more knowledgeable about the bean quality they can sell.